Metodologías más eficientes para determinar la viabilidad ambiental de la tecnología de pirolisis de llantas usadas en Colombia (2018)
In the present monograph the scientific review on the pyrolysis process is advanced, from the collected information possible alternatives of use of used tires are presented, wanting to notice the dilemma when applying the technology of pyrolysis, a waste is reused, but at the same time a series of critical environmental impacts are triggered in greater proportion than those originally generated by the inadequate disposal of used tires. Six methodologies are analyzed for the environmental impact study and one of these is determined as the most appropriate for the pyrolysis process, applying it theoretically to the process and determining its environmental viability.